Do African Leaders Deliver on their Election Promises? A Case of Fetakgomo-Tubatse Municipality, Limpopo Province - Matsimela, A. R.; Kanjere, M. M. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The study focused on the failure of the local municipality under the leadership of the ANC as the ruling party, to provide clean water to the households. Provision of clean water has remained a key element in the manifesto of the ANC over the years, and also in the current 2019 election campaigns, however, this aspect has been eluding the party over the years. This is in contrast to the legislation which states that Provincial and Local Government Municipalities should provide un-interrupted quality water services to citizens. The Constitution of the Republic of South Africa, in particular, chapter two (Bill of Rights) sections 27(1) (b) enshrines the basic right of access to sufficient water, as well as a safe and healthy environment. Furthermore, the constitution obliges government, in particular Municipalities as water service providers to meet their constitutional responsibility of providing healthy drinking water services to the communities. The other major piece of current legislation is the National Water Act, 36 of 1998, chapter 2, water management strategies that delineates how water resources need to be protected, used, developed, conserved, managed and controlled. Chapter 3, part 3, further deals with water reserve which consist of two parts and they are, the basic human need reserve and the ecological reserve. The basic human need reserve provides for the essential needs of individuals served by water resource in question and includes water for drinking, for food preparation and for personal hygiene. The ecological reserve relates to the water required to protect aquatic ecosystems of the water resource. This has to be primarily within the guiding principles of sustainable development and for the benefit of everyone in South Africa.
Article published in the 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Bulk water supply; Framework; Service delivery; Water quality; Water resources; Municipal services--South Africa; Water-supply